2003
DOI: 10.1042/bj20021208
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Gbeta3s2, a novel splice variant of the G-protein beta3 subunit

Abstract: The T-allele of a polymorphism (C825T) in the gene for the G-protein beta 3 subunit (GNB3) is associated with cardiovascular and metabolic disorders, distinct cellular features and altered drug responses. The molecular mechanisms that give rise to this complex phenotype have been linked to the occurrence of G beta 3s, a splice variant of GNB3. G beta 3s is predominantly expressed in cells with the 825T-allele. In the present study we describe the identification and characterization of an additional G beta 3 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 52 publications
1
41
0
1
Order By: Relevance
“…Evidence from transient-expression experiments suggests that Gb3s is a biologically active protein that enhances signal transduction. 3,16,17 Recently, Rosskopf et al 18 reported that Gb3s-containing G protein results in an increased number of activated Gas and free Gbg dimers, which subsequently activate the downstream effector systems.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from transient-expression experiments suggests that Gb3s is a biologically active protein that enhances signal transduction. 3,16,17 Recently, Rosskopf et al 18 reported that Gb3s-containing G protein results in an increased number of activated Gas and free Gbg dimers, which subsequently activate the downstream effector systems.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this polymorphism is associated with the occurrence of two alternative splice variants termed Gβ3s and Gβ3s2 ( Fig. 16; Rosskopf et al 2003a). Protein crystallization studies have resolved the structure of the Gβγ dimer.…”
Section: Genetic Variants In the Gene For The Gα Subunit (Gnas) And Tmentioning
confidence: 99%
“…A second aberrant splicing process was also identified which affects exon 10 (in which the C825T polymorphism is located) giving rise to a splice variant referred to as G␤3-s2. (20). By means of RT-PCR this splice variant was detected in human heart, T cells, neutrophils, peripheral blood lymphocytes, and bladder carcinoma predominantly in cells and tissues from 825T allele carriers (20).…”
mentioning
confidence: 99%
“…(20). By means of RT-PCR this splice variant was detected in human heart, T cells, neutrophils, peripheral blood lymphocytes, and bladder carcinoma predominantly in cells and tissues from 825T allele carriers (20).…”
mentioning
confidence: 99%